States and Women's Rights - Safoi Babana-Hampton (International Institute of Islamic Thought, 2002)
In her preface, Mounira Charrad traces the genesis of her study to her concerns as a sociologist regarding the inadequate analytical models used to account for the origin of political organization in the "predominantly classbased and capitalist societies" Maghribi societies. Charrad proposes "kinship" and tribal ties as more appropriate sociological categories for acquiring a good understanding of the foundations of social relations in Tunisia, Algeria, and Morocco. She focuses on three distinct historical periods: precolonial, colonial, and post-independence. Her investigation centers on documenting the historical relationship between the process of nationbuilding and state-formation, and the codification and articulation of a unified family law that replaced numerous (and sometimes conflicting) forms of customary law competing with Islamic law. The book combines historical, sociological, and geographical data and analytical concepts in order to frame the investigation's main subject. The subject is covered in three main parts divided into nine chapters, in addition to an introduction and a conclusion. The text is supplemented with tables and maps documenting linguistic and geographic features of the Maghrebi states under study. The book concludes with a useful glossary of transliterated Arabic words, chapter notes, a selected bibliography organized conveniently under five main headings, an author index, and a subject index ...